121k views
1 vote
Find the third term of a geometric progression if the sum of the first three terms is equal to 12, and the sum of the first six terms is equal to (−84).

User Teivaz
by
4.9k points

1 Answer

5 votes

Given:

The sum of the first three terms = 12

The sum of the first six terms = (−84).

To find:

The third term of a geometric progression.

Solution:

The sum of first n term of a geometric progression is:


S_n=(a(r^n-1))/(r-1)

Where, a is the first term and r is the common ratio.

The sum of the first three terms is equal to 12, and the sum of the first six terms is equal to (−84).


(a(r^3-1))/(r-1)=12 ...(i)


(a(r^6-1))/(r-1)=-84 ...(ii)

Divide (ii) by (i), we get


(r^6-1)/(r^3-1)=(-84)/(12)


((r^3-1)(r^3+1))/(r^3-1)=-7


r^3+1=-7


r^3=-7-1


r^3=-8

Taking cube root on both sides, we get


r=-2

Putting
r=-2 in (i), we get


(a((-2)^3-1))/((-2)-1)=12


(a(-8-1))/(-3)=12


(-9a)/(-3)=12


3a=12

Divide both sides by 3.


a=4

The nth term of a geometric progression is:


a_n=ar^(n-1)

Where, a is the first term and r is the common ratio.

Putting
n=3,a=4,r=-2 in the above formula, we get


a_3=4(-2)^(3-1)


a_3=4(-2)^(2)


a_3=4(4)


a_3=16

Therefore, the third term of the geometric progression is 16.

User Tashay
by
5.2k points